1991
DOI: 10.1002/ijc.2910480308
|View full text |Cite
|
Sign up to set email alerts
|

Oncofetal expression of the human intestinal mucin glycoprotein antigens in gastrointestinal epithelium defined by monoclonal antibodies

Abstract: A mucin preparation from a colonic adenocarcinoma was used to prepare monoclonal antibodies (MAbs) that reacted specifically either with normal adult small-intestine mucin antigen(s) (SIMA), or normal adult large-intestine mucin antigen(s) (LIMA). Both SIMA and LIMA show a unique oncofetal pattern of expression. Thus SIMA was expressed in early fetal stomach, large and small intestines but thereafter only in the normal small intestine. SIMA expression was detected immunohistochemically in cancers of the colore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 17 publications
0
37
0
Order By: Relevance
“…In terms of epitope structure, previous studies have shown that the four anti-SIMA MAbs recognise distinct neuraminidase-sensitive carbohydrate epitopes, two which are distinct from sialosyl-Tn and 2 which partially cross-react (Hertzog et al, 1991a;Pilbrow et al, 1992a). Additive ELISAs have suggested that MAb 4D3 recognises a core carbohydrate structure, and the other three MAbs, more peripheral epitopes (Pilbrow et al, 1992a).…”
Section: Metaplastic Polypsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of epitope structure, previous studies have shown that the four anti-SIMA MAbs recognise distinct neuraminidase-sensitive carbohydrate epitopes, two which are distinct from sialosyl-Tn and 2 which partially cross-react (Hertzog et al, 1991a;Pilbrow et al, 1992a). Additive ELISAs have suggested that MAb 4D3 recognises a core carbohydrate structure, and the other three MAbs, more peripheral epitopes (Pilbrow et al, 1992a).…”
Section: Metaplastic Polypsmentioning
confidence: 99%
“…Anti-SIMA MAb 4D3 and anti-LIMA MAb 2C3 were prepared by immunisation of mice with a mucin extract from a colorectal cancer (Hertzog et al, 1991a and b), and anti-SIMA MAb 3D4, 5C5 and 6C5 by immunisation with a mucin extract of post-mortem tissue from normal adult small intestine (Pilbrow et al, 1992a in three areas where present: neoplastic adenoma tissue, base of adenoma and immediately adjacent perineoplastic mucosa. A previously described scoring method was used: a score of 0-3 was given for staining intensity and similarly, for distribution [0 (negative, 1 (<25% of crypt positive), 2 (25-75%) or 3 (75-100%)].…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
“…Mucin extraction andfractionation Mucins were extracted from specimens of resected cancers or normal gastrointestinal tract using 4 M guanidine hydrochloride in phosphate buffered saline (PBS), containing the protease inhibitors: 10 mm N-ethyl maleimide, 1 mM benzamidine hydrochloride, and 25 mM EDTA (Hertzog et al, 1991). Homogenates were centrifuged at 20,000 x g for 20 min, and the supernatants subjected to three cycles of CsCl density gradient centrifugation for purification of mucin fractions.…”
Section: Methodsmentioning
confidence: 99%
“…Mucin glycoproteins have also been demonstrated to be differentiation-associated or oncofetal antigens in the gastrointestinal tract (Gold & Miller, 1978;Ma et al, 1980;Bara et al, 1980;Hertzog et al, 1991). Similar abnormalities of mucin glycoprotein expression have also been identified in other epithelial tissues, including the breast (Griffiths et al, 1987) and ovary (Bhattacharya et al, 1982).…”
mentioning
confidence: 92%
See 1 more Smart Citation